Evolution of deformation mechanisms and their orientation dependence in fine-grained Mg-3Gd during tension - Faping Hu; Tianbo Yu; Hao Chen; Fang Han; Keshun Dai; Fangcheng Qiu; Weidong Xie; Xiaoxu Huang (Journal of Magnesium and Alloys)
Magnesium alloys usually exhibit poor ductility attributed to their intrinsic hexagonal close-packed (hcp) structure, which fails to provide sufficient independent slip systems for homogeneous deformation. Here we demonstrate that multiple deformation mechanisms can be activated with increasing tensile strain in a fine-grained Mg-3Gd with a weak basal texture. 〈c + a〉 slip, tension twinning and compression/double twinning exhibit a high orientation dependence at an early stage of deformation, whereas the orientation dependence becomes less obvious with further increasing strain. The high work hardening rate at the strain of 2%–5% is accompanied by the significant increase of 〈c + a〉 slip and tension twinning activities. The fine microstructure strongly restricts the activation and growth of twinning, resulting in a slow exhaust of tension twinning and thin compression twins. The restriction of twinning and the activation of profuse 〈c + a〉 slip near grain/twin boundaries, relaxing the stress concentration, sustain the homogeneous deformation to a high strain.